THE ROLE OF EMOTIONS IN MUSIC EDUCATION: THEORETICAL INSIGHTS - Rauduvaitė, Asta; Yao, Zhiyu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Emotional expression has been the focus of teachers and educational researchers, as it can result in an improvement in cognitive performance. In specific settings, personal and emotional experiences can provide a steppingstone to developmental and learning processes. Emotions significantly influence learner learning and play a crucial role in quality teaching, educational reform, and learner-teacher interaction. The inherent social and communicative nature of music would make group training an excellent tool for increasing the coordination of behaviour, affect, and mental states among children. This paper aims to explore the literature on various aspects of the concept of emotions in the context of music education with the main focus on opportunities for experiencing and expressing emotion in music education, learners' positive emotion experiences in music education, teaching to generate positive emotion outcomes, and the benefits of a greater emphasis on the emotions in music education. The results of theoretical analysis indicate that music education has a particularly positive effect on identifying emotions, emotion regulation, emotion recognition, improved learning, and self-expression.